Smart campus: implementation of energy innovations in the educational environment - Okushko, O.; Radko , I.; Nalyvaiko, V. (Energy and Automation, 2026)
The article considers approaches to increasing the energy efficiency of higher education institutions in the context of digitalization using the example of the implementation of the Smart Campus concept at the National University of Life Resources and Environmental Sciences of Ukraine. The main attention is paid to the use of automated energy monitoring systems that provide continuous control of electricity and heat consumption in real time. The possibilities of using the collected data for modeling and forecasting energy consumption, taking into account technical, climatic and behavioral factors, are analyzed. It is shown that the integration of digital tools allows you to identify inefficient operating modes of engineering systems, optimize loads and reduce energy consumption. The results of studies of the dynamics of energy consumption in educational buildings and dormitories are presented, which demonstrate the adaptability of the system to changes in operating conditions and user stay modes. The effectiveness of the use of analytical and predictive models to improve the quality of energy management and reduce energy and financial risks is substantiated. It was established that the implementation of energy monitoring systems contributes to reducing energy consumption, increasing the energy efficiency of buildings and forming a culture of rational use of resources. The educational and scientific value of the system as a tool for training specialists in the field of energy management and digital energy technologies is also emphasized. Recieved 2025-11-17 Recieved 2026-01-09 Accepted 2026-02-11